PSVI-2 Rising 10-year Trend in Piglet Pre-weaning Mortality in Breeding Herds Associated with Sow Herd Size and Number of Piglets Born Alive - Koketsu, Yuzo (J Anim Sci, 2021)
The objectives of the present study were to explore the trend in preweaning mortality (PWM) and related measurements such as piglets born alive (PBA), stillborn piglets, herd productivity and herd size in sow herds over a 10-year period; and 2) to examine the relationships between PWM and the related measurements. Herd-level annual data from 2007–2016 for 91 herds in Spain were abstracted from a sow database compiled by a veterinary consultancy firm. The database software automatically calculated herd-level PWM (%) as follows: the total number of piglets born alive to a sow completely weaned during a year (TPBA) minus the total number of piglets weaned by the completely weaned sow during the year divided by TPBA x 100. All the statistical analyses were performed using SAS University Edition. A growth curve model was applied to incorporate correlations for all of the observations arising from the same farm. Herd means of PWM (SD) increased from 11.9 (4.1) % to 14.4 (3.2) %, and mean PBA increased by 1.9 pigs. Mean age of piglet death during lactation increased by 3.8 days, and there was a significant effect of increased year on herd size and the number of piglets weaned per sow per year (PSY; P < 0.05). Higher PWM was associated with more PBA, more stillborn piglets and small herds (lower than the median size: < 570 sows; P < 0.05). Also, as PBA increased from 9 to 14 pigs, PWM in large herds (> 570 sows) increased by only 6.6%, compared with 9.6% in small herds. Furthermore, as PWM decreased from 18 to 8%, herd productivity measured as PSY increased by 2.2 pigs in large herds, but only by 0.6 pigs in small herds. In conclusion, the effect of increased PBA on PWM was alleviated more in large herds than in small herds. Also, the impact of decreased PWM on herd productivity was greater in large herds than in small herds.